Industry 4.0: critical investigations and synthesis of key findings - Elnadi, Moustafa; Abdallah, Yasser Omar (Springer, 2024)
The concept of Industry 4.0 has been one of the most debated and trending topics over the last few years. Progressively, it has attracted the attention of academicians, practitioners, and policymakers worldwide. However, there needs to be more systematic review of research in the current literature that captures the current state of this new paradigm. This study aims to address this gap by conducting a comprehensive review of Industry 4.0 previous studies to identify its technological, organisational, and managerial enablers, as well as its implementation challenges and benefits. A systematic literature review was conducted, in which 244 peer-reviewed journal papers were analysed in the Scopus database until the end of May 2022. This study excluded conference papers, book chapters, and journal papers not written in English. The study indicated that industry 4.0 is still an immature topic, and applying this new paradigm is not a matter of technology only. Organisational and managerial aspects should be considered. Additionally, the transition towards Industry 4.0 is a complex task, many obstacles exist, and manufacturing companies should be aware of these challenges for successfully implementing this new paradigm. The obtained results in this study synthesise recent studies published on Industry 4.0 and provide a comprehensive picture of Industry 4.0 and potential research directions for future research. Also, this study offers significant guidelines for managers interested in implementing Industry 4.0.
Keywords: Industry 4.0; Digitisation; Review; Fourth industrial revolution